The functions of long noncoding RNAs on regulation of F-box proteins in tumorigenesis and progression - Xia, Lu; Chen, Jingyun; Huang, Min; Mei, Jie; Lin, Min (Frontiers in Oncology, 2022)
Accumulated evidence has revealed that F-box protein, a subunit of SCF E3 ubiquitin ligase complexes, participates in carcinogenesis and tumor progression via targeting its substrates for ubiquitination and degradation. F-box proteins could be regulated by cellular signaling pathways and noncoding RNAs in tumorigenesis. Long noncoding RNA (lncRNA), one type of noncoding RNAs, has been identified to modulate the expression of F-box proteins and contribute to oncogenesis. In this review, we summarize the role and mechanisms of multiple lncRNAs in regulating F-box proteins in tumorigenesis, including lncRNAs SLC7A11-AS1, MT1JP, TUG1, FER1L4, TTN-AS1, CASC2, MALAT1, TINCR, PCGEM1, linc01436, linc00494, GATA6-AS1, and ODIR1. Moreover, we discuss that targeting these lncRNAs could be helpful for treating cancer via modulating F-box protein expression. We hope our review can stimulate the research on exploration of molecular insight into how F-box proteins are governed in carcinogenesis. Therefore, modulation of lncRNAs is a potential therapeutic strategy for cancer therapy via regulation of F-box proteins.